PERAN CORPORATE SOCIAL RESPONSIBILITY (CSR) MELALUI PROGRAM MEKAAR PT.PNM PADA IRT PRASEJAHTERA DI DESA SIDOMULYO KECAMATAN MEDANG DERAS - Mahfuzi Irwan; Elsa Laurenza Romauli Hutahaean (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2024)
This research aims to analyze the role of Corporate Social Responsibility at PT. PNM was implemented through the Prosperous Family Economic Developments (Mekaar) Program for Underprivileged Housewives (IRT) in Sidomulyo Village, Medang Deras District. This study used a descriptive qualitative method. The subjects in this research were 4 people consisting of 1 Accounting Officer (AO) or field employee of PNM Mekaar and 3 Underprivileged housewives as customers of PNM Mekaar, Sidomulyo Village, Pasar Baru Hamlet. Data collection in this research used interviews, observation, and documentation techniques. Data analysis techniques are carried out by data reduction, data presentation, and conclusion. Data validity was carried out using source triangulation and method triangulation. The results of the study indicate that the role of Corporate Social Responsibility at PT. PNM implemented through the Prosperous Family Economy Development Program (Mekaar) for Underprivileged Housewives (IRT) in Sidomulyo Village, Medang Deras District was implemented by implementing business capital loans and strengthened by women's empowerment activities. Business capital loans help underprivileged Housewives (IRT) in starting or developing micro-businesses, while women's empowerment involves them in activities that encourage economic independence and women's emancipation. Overall, PNM has succeeded in carrying out its social responsibility in developing the community economy and empowering women in the area.